Krakatau: The Tale of Lampung Submerged, Syair Lampung Karam - H., Aveling (Penerbit Universiti Sains Malaysia (USM Press), 2016)
There are over a thousand European studies of the world famous explosion of Krakatau (or Krakatoa) in August 1883, mainly of a geological nature. The book under review presents a contemporary firsthand account by an Indonesian/Malay author of the effects of the event on the local inhabitants of South Sumatra and Northwestern Java. It is written in the verse form known as syair.